Prisons and women /Blanche Hampton. - Hampton, Blanche,1956-
"This is a project supported by grants from the Criminology Research Council and the Mercy Foundation Ltd. under the auspices of Women and Girls in Custody, a subcommittee of the New South Wales Prisons Coalition."--T.p. verso.